Genetic diversity and phylogenetic relationships of Calotes and Uromastyx in the Cholistan Desert, Pakistan, based on COI gene analysis. - Javed Hussain; Gulnaz Afzal; Muhammad Zeshan Haider; Iram Qadeer; Shazia Perveen; Hafiz Ishfaq Ahmad; Ahmed A El-Mansi; Abdelalim A Gadallah; Kasim Sakran Abass (PLoS ONE)
The Cholistan Desert of Pakistan harbors unique reptile diversity, including ecologically significant agamid lizards of the genera Calotes and Uromastyx, yet their genetic structure remains poorly understood. This study presents the first mitochondrial DNA barcode assessment of these taxa in the region, analyzing 658 bp of the cytochrome c oxidase I (COI) gene from 19 specimens collected across seven desert sites. We employed a combination of distance-based (p-distance, K2P) and phylogenetic methods (Maximum Likelihood, Bayesian Inference) to evaluate genetic diversity and evolutionary relationships. Results revealed pronounced divergence between genera (24-30% K2P distance), with Uromastyx populations showing remarkably low intraspecific variation (0-1%), contrasting with higher diversity in Calotes (0-14%). Demographic analyses suggested stable populations (Tajima's D = 0.93, p > 0.10), though haplotype networks indicated limited gene flow (Nm = 0.12). Our findings: (1) provide the first genetic baseline for these ecologically important desert lizards, (2) identify Uromastyx as potentially more vulnerable to genetic erosion, and (3) demonstrate the utility of COI barcoding for rapid biodiversity assessment in understudied arid ecosystems. The study highlights the Cholistan Desert as an evolutionary significant zone for agamid lizards while underscoring the need for integrated taxonomic approaches to address potential cryptic diversity. All sequence data are publicly available (GenBank PQ896696-PQ896705) to support future conservation genomic studies.